2022
DOI: 10.3390/radiation2040027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ion Cyclotron Frequencies on Human Resistance and Reactance in 31 Healthy Subjects

Abstract: In order to test the theory of Brizhik et al. about the dynamic allocation of acupuncture meridians on human body and their role as hydric paths for solitons, we tested the effect of both acupuncture and exposure to extremely low frequencies (ELF) tuned with suitable ion cyclotron frequencies. The similarity of the effects, inducing variations of body impedance measured in well-known acupuncture points, up to the interchangeability and the synergy of the two treatments, the mechanic and the electromagnetic one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This mechanism is assumed to be associated with resonances of ions that regulate the rate of biochemical reactions in the cells of biological systems. It is described in the scientific literature as cyclotron resonance [74][75][76][77][78][79][80]. Laboratory data demonstrate the influence of the ion cyclotron mechanism on the regulation of isolated myocardial cells [81].…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism is assumed to be associated with resonances of ions that regulate the rate of biochemical reactions in the cells of biological systems. It is described in the scientific literature as cyclotron resonance [74][75][76][77][78][79][80]. Laboratory data demonstrate the influence of the ion cyclotron mechanism on the regulation of isolated myocardial cells [81].…”
Section: Discussionmentioning
confidence: 99%
“…It is easy to check that from the classical Hamilton equations ṙc = (∂H/∂p) p=pc and ṗc = −(∂H/∂r) r=rc , where H is determined by the expression (9), the system of equations ( 3), ( 6) and ( 7) follows. Now making the usual replacements p z → pz = −ih∂/∂z and p ⊥ → p⊥ = −ih∇ ⊥ in (9), where is h the Planck's constant and ∇ ⊥ is the transverse gradient, we write the non-stationary Schrödinger equation in the coordinate representation:…”
Section: Quasi-classical Hamiltonian Approachmentioning
confidence: 99%
“…The phenomenon of cyclotron resonance consists of a sharp increase in the absorption of electromagnetic waves by charged particles when the frequency ω of these waves is equal to the frequency ω B of rotation of charged particles around a constant magnetic field [1][2][3]. This effect is observed in conducting media, including metals [4], semiconductors [5][6][7], plasma [8], gases, organic compounds [9], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Wang et al [117] evaluated "micro-clustered water (MC)," or structured drinking water, on the hydration status in humans. They found that diabetes patients who drank micro-clustered water had improved cell water distribution (ICW/ECW), basal metabolism rate (BMR), phase angle (PA), and cell capacitance (CP) during the four-week study.…”
Section: Effects Of Drinking Sw Water On Health and Longevitymentioning
confidence: 99%